Flexible Penal Legislative Drafting and Its Impact on Intellectual Freedoms - Hamoud, Alaa; Al-Ameri, Samer (Journal of Legal Sciences, 2026)
Public freedoms are considered an embodiment of the rule of law, the most important of which is intellectual freedoms, because individuals cannot exercise their freedoms in isolation from intellectual freedoms, They are enshrined in various charters and declarations of human rights, as enshrined in most constitutions, including the Constitution of the Republic of Iraq 2005, and its philosophy is that it is an interaction between the individual and society as it benefits individuals and society and this is due to its nature, It is the duty legislator, specifically in the criminal law, to protect public freedoms and place restrictions on them to prevent their conflict with the freedoms of others, However, flexible criminal legislative wording may sometimes intersect with the principles of the constitution, and thus produce effects that may exterminate the essence of intellectual freedoms, and make their exercise impossible, which entails some legal treatments that we touched in the research.